Improvement in Sensorineural Hearing Loss During Pregnancy. (September 2014) - Stevens, Madelyn N.; Hullar, Timothy E.
Objective: Hearing loss is known to occur in some pregnant women, but improvement in sensorineural thresholds has not been audiometrically characterized. Here, we describe a patient with a history of Ménière's disease and vestibular migraine who experienced temporary recovery of her hearing during pregnancy. Methods: Audiograms were obtained from a 31-year-old female over the course of 2 successive pregnancies. Results: Audiograms revealed a substantial improvement in hearing by the third trimester during each pregnancy, with a rapid return to baseline thresholds after delivery. Conclusion: This case is unique in documenting improvements in hearing thresholds during pregnancy and substantiates the effects of hormonal changes on hearing thresholds in humans. It raises the intriguing possibility of hormonal therapy as a treatment for sensorineural hearing loss in specific clinical situations.